Into-A or into-B, that is a question: a systematic literature review of directionality and performance in consecutive interpreting - Lu, Rong; Abdullah, Muhammad Alif Redzuan; Ang, Lay Hoon (SAGE Publications, 2023)
Although the debate over the into-A and into-B interpreting has never stopped, the focal point was mostly set on simultaneous interpreting and sign language interpreting. Directionality in consecutive interpreting (CI) has not been studied fully so far. The present systematic literature review was designed to examine the relationship between directionality and performance in CI across a wide range of settings and empirical methods based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and search for articles in English in Scopus and Web of Science. Three problems were investigated in the current research: (i) How does directionality impact performance among professional and student interpreters in CI? (ii) What factors contribute to the effect of directionality on performance? (iii) Does directionality preference impact the interpreter’s performance? The findings include: (i) directionality proves to influence the performance of interpreters whose A- and B-languages are not equally proficient, whereas balanced bilinguals are not affected by directionality; (ii) both internal and external factors contribute to the interpreters’ performance; (iii) only descriptive studies about interpreters’ directionality preference were identified in the prior literature, and a further study with more focus on the interactive power of directionality preference on interpreters’ performance is required.